Urgensi Pendidikan dan Pengajaran Akhlak (Budi Pekerti) Sebagai Pondasi Dalam Perspektif Islam - Kasron Kasron (Al-Ulum: Jurnal Pendidikan Islam, 2021)
The problem is, so far we have actually carried out moral education, both at home and in formal educational institutions, such as madrasas and schools. In the Law on the National Education System itself, it is explicitly stated that one of the objectives of implementing national education is to form human beings with noble character. However, it seems that we 'failed' in forming human beings with noble character. The phenomenon as described above is one proof of this 'failure'. Therefore, observing this, the discussion and discussion about moral education is increasingly finding its urgency. Because, one of the crucial problems that must be responded to and overcome by the world of education, especially Islamic education, is the problem of moral education.Keywords: Ruju’, Hukum Islam, Ushul Fikih